1995
DOI: 10.1177/039139889501800604
|View full text |Cite
|
Sign up to set email alerts
|

Blood Platelet Activation and Membrane Glycoprotein Changes during Extracorporeal Life Support (Ecls). In Vitro Studies

Abstract: The aim of this study was to evaluate an in vitro model for investigation of platelet function parameters in an extracorporeal system. Two different perfusion pumps were compared, a roller pump (Polystan) and a centrifugal pump (Biomedicus). A continuous increase in glycoprotein (GP)1b-negative platelets was observed in both circuits. A marked increase of plasma beta-thromboglobulin thromboglobulin concentration and a decrease of the intracellular pool of serotonin was observed, indicating a marked release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…By utilizing NO as the agent being released from the diazeniumdiolated polymer in this study, the degree of thrombosis and ECC-induced expression of platelet P-selectin and monocyte CD11b were attenuated. Much of ECLS research has previously shown a decrease in the levels of thrombosis and an underlying threshold level of locally-released NO from either polyvinyl chloride (PVC) or polyurethane (PU)-based polymers [25,26,5658]. Skrzypchak et al, in particular, had shown that the NO donor, DBHD/N 2 O 2 released an amount of NO from the PVC polymer that preserved platelet number and maintained their ability to aggregate upon stimulation with exogenous collagen [26].…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing NO as the agent being released from the diazeniumdiolated polymer in this study, the degree of thrombosis and ECC-induced expression of platelet P-selectin and monocyte CD11b were attenuated. Much of ECLS research has previously shown a decrease in the levels of thrombosis and an underlying threshold level of locally-released NO from either polyvinyl chloride (PVC) or polyurethane (PU)-based polymers [25,26,5658]. Skrzypchak et al, in particular, had shown that the NO donor, DBHD/N 2 O 2 released an amount of NO from the PVC polymer that preserved platelet number and maintained their ability to aggregate upon stimulation with exogenous collagen [26].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Indeed, already during the first minutes of perfusion, contact between blood and biomaterial induces an activation of various cascade systems. 3,5,6 Over the past few years, much effort has been devoted to improving the biocompatibility of extracorporeal systems, e.g. the use of heparinized perfusion circuits?…”
Section: Introductionmentioning
confidence: 99%
“…Most likely, these re-appearing platelets have lost much of their a-granula content, and circulate as nonfunctional platelet ghosts. 1 We conclude that albumin priming appears to prevent platelet activation during long-term extracorporeal circulation. Furthermore, albumin coating might even reduce the initial adherence of platelets to the foreign material of the circuit.…”
Section: Discussionmentioning
confidence: 71%
“…The bleeding complications seen in association with ECMO treatment have been attributed to the systemic heparinization, as well as to an induced thrombocytopenia and platelet dysfunction. 1 Albumin coating is routinely used to passivate the surfaces of extracorporeal perfusion systems and it has been assumed that this treatment preserves the platelets and inhibits platelet adhesion to the artificial surfaces. However, this effect of albumin priming has, to our knowledge, not been demonstrated under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%